2022
DOI: 10.1021/acs.analchem.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Hemin into Metal–Organic Frameworks: Mimicking Natural Peroxidase Microenvironment for the Rapid Ultrasensitive Detection of Uranium

Abstract: Constructing enzyme-like active sites in mimic enzyme systems is critical for achieving catalytic performances comparable to natural enzymes and can shed light on the natural development of enzymes. In this study, we described a specific hemin-based mimetic enzyme, which was facilely synthesized by the assembly of zeolitic imidazolate framework-L (ZIF-L) and hemin. The obtained hemin-based mimetic enzyme (denoted as ZIF-L-hemin) displayed enhanced peroxidase activity compared to free hemin in solution. Such ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The controlled results in Figure A have indicated that individual AuNPs or FeTCPP does not possess oxidase-mimicking activity, which is consistent with earlier studies. , In CYP, the metallo-porphyrin has the ability to activate molecular oxygen. , Unlike heme-containing oxygenases, iron porphyrin nanozymes cannot activate oxygen due to the inappropriate coordination and the ferric state of ions since the delicate local microenvironment around iron porphyrin is absent. Thus, iron porphyrin nanozymes have exhibited only peroxidase-mimicking activity but no oxidase-like activity up to now. Loading FeTCPP on AuNP supports in the presence of Al 3+ can significantly alter the microenvironment around FeTCPP, which contributes to substrate binding and activation (Scheme ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The controlled results in Figure A have indicated that individual AuNPs or FeTCPP does not possess oxidase-mimicking activity, which is consistent with earlier studies. , In CYP, the metallo-porphyrin has the ability to activate molecular oxygen. , Unlike heme-containing oxygenases, iron porphyrin nanozymes cannot activate oxygen due to the inappropriate coordination and the ferric state of ions since the delicate local microenvironment around iron porphyrin is absent. Thus, iron porphyrin nanozymes have exhibited only peroxidase-mimicking activity but no oxidase-like activity up to now. Loading FeTCPP on AuNP supports in the presence of Al 3+ can significantly alter the microenvironment around FeTCPP, which contributes to substrate binding and activation (Scheme ).…”
Section: Resultssupporting
confidence: 88%
“…Iron porphyrins are widely present as active sites in many natural enzymes, and oxygen reduction catalyzed by porphyrins has been of great interest in biological systems. Iron porphyrin-based nanozymes have received great interest because of their potential applications in environmental and biological fields. Unfortunately, hemin-based nanozymes only have been demonstrated to display peroxidase-mimicking properties, but no oxidase-mimicking properties capable of reversibly binding dioxygen at ambient temperature and neutral pH. Free heme is fast-oxidized into ferric hemin in air, so earlier studies about heme-containing nanozymes did not address a direct correlation between the ferrous heme and oxygen activation. Furthermore, different from natural oxygenases (e.g., cytochrome P450s (CYP)), heme nanozymes have no proper microenvironment around active sites for substrate activation because of the absence of a precise structure.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the key analytical properties of the U-pT-12 sensor and several previously reported U(VI) sensors and detection methods [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The LOD of the current sensor compares well with several other U(VI) sensors, including colorimetric, SERS, and electrochemical sensors [ 11 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the key analytical properties of the U-pT-12 sensor and several previously reported U(VI) sensors and detection methods [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The LOD of the current sensor compares well with several other U(VI) sensors, including colorimetric, SERS, and electrochemical sensors [ 11 , 13 , 14 , 15 ]. Although there are sensors with significantly lower LODs [ 10 , 12 ], these sensors require custom designed and synthesized U(VI)-specific ligand and/or nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation